Perioperative Vasopressors are Associated with Delayed Graft Function in Kidney Transplant Recipients in a Primarily Black and Hispanic Cohort. (June 2022) - Benken, Jamie; Lichvar, Alicia; Benedetti, Enrico; Behnam, Jessica; Kaur, Arashpreet; Rahman, Syeda; Nishioka, Hokuto; Hubbard, Colin; Benken, Scott T.
Introduction: Negative outcome studies of vasopressors in kidney transplant have not focused on patient populations that are predominantly Black or Hispanic. ProjectAims: The evaluation sought to investigate the independent impact of perioperative vasopressors on postoperative renal allograft function in a sample drawn from a primarily Black and Hispanic population.Design: Retrospective, observational, single-center evaluation of patients > 18 years old who underwent kidney transplantation comparing outcomes based on vasopressor exposure.Results: The study included 150 patients of which 60 received vasopressors. The primary outcome differed between groups with delayed graft function occurring in 17(28%) versus 11(12.2%) occurring more often in those that received perioperative vasopressors (P = 0.02). The serum creatinine at postoperative day 7 was higher (2.69 vs1.52 mg/dL, P = 0.004), postoperative day 7 eGFR was worse (27.3 vs 52.9 mL/min/1.73m2, P = 0.002) in patients who received vasopressors. Patients who received perioperative vasopressors experienced more postoperative arrhythmias (15% vs 8%, P = 0.007), insulin infusion therapy (26.7% vs 13.3%, P = 0.04), and increased hospital length of stay (6 days vs 5 days, P = 0.006). Using IPWRA, patients receiving vasopressors were more likely to experience delayed function, relative risk difference of 22% (95% CI:0.08-0.35;P = 0.002) and in multivariate logistic regression modeling, an increased odds ratio of 3.2 (95% CI:1.1-8.62;P = 0.022).Conclusions: The use of perioperative vasopressors was independently associated with worsened early renal allograft function including delayed graft function, increased adverse events such as postoperative arrhythmias, and longer ICU length of stay. Further investigation is needed surrounding vasopressor use in this population.